Anchoring Black Phosphorus Quantum Dots on Fe‐Doped W18O49 Nanowires for Efficient Photocatalytic Nitrogen Fixation. Issue 30 (7th June 2022) - Dong, Guojun; Huang, Xiaojuan; Bi, Yingpu
Abstract: Herein, we demonstrate that the surface anchoring of black phosphorus quantum dots (BPQDs) and bulk iron‐doping in W18 O49 nanowires significantly promotes the photocatalytic activity toward N2 fixation into NH3 . More specifically, a NH3 production rate of up to 187.6 μmol g −1 h −1 could be achieved, nearly one order of magnitude higher than that of pristine W18 O49 (18.9 μmol g −1 h −1 ). Comprehensive experiments and density‐functional theory calculations reveal that Fe‐doping could enhance the reducing ability of photo‐generated electrons by decreasing the work function and elevating the defect band (d‐band) centers. Additionally, the surface BPQDs anchoring could facilitate the N2 adsorption/activation owing to the increased adsorption energy and advantaged W−P dimer bonding‐mode. Therefore, synergizing the surface BPQD anchoring and bulk Fe‐doping remarkably enhanced the photocatalytic activity of W18 O49 nanowires for NH3 production. Abstract : Anchoring black phosphorus quantum dots on Fe‐doped W18 O49 nanowires significantly promoted the photocatalytic performances for N2 fixation into NH3 .